Pola Pembelajaran Epistemik Terintegrasi STEAM+X dalam Pembelajaran Rasio - Isnawan, Muhamad Galang; Zulhidayati, Indah; Jannah, Siti Wardatul; Mahirudin, Mahirudin; Lidaini, Lidaini (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
The concept of ratio is a fairly important mathematical concept, but it remains a persistent challenge for students. Therefore, this study aimed to optimize 3D representation skills and learning drive by developing epistemic learning patterns integrated with STEAM+X. X referred to aspects of history, culture, and architecture. The research design used was design-based research. Participants in this study consisted of 21 stakeholders in the field of education (teachers, school principals, and academics). The instruments used were a phenomenological questionnaire to explore the causes of students experiencing problems and an integrated STEAM+X ELP module to optimize student competence. The data were analyzed using a combination of thematic analysis and qualitative data analysis. The results revealed that there were five factors that caused low levels of both competencies, namely identity and orientation crisis, spatial experience deficit, motivation and engagement crisis, pedagogical mismatch, and ecosystem limitations. The solutions offered were a student-centered approach, technology and innovation, active and experiential learning, and ecosystem support. All of these components were represented in the form of an integrated STEAM+X ELP module, with the main activity referring to the Subak Lingsar miniature project. Subak Lingsar was chosen because it could support student learning of ratios, such as scale and the rate of change of water flow, as well as comparisons of value and inverse value. This study recommended that the module be implemented in the context of ratio learning by testing its impact on students’ 3D representation abilities and learning drive in schools.